(untitled) (Research, Society and Development, 2021)
Objective: to report the experience of a workshop on hand hygiene with health professionals from a hospital unit. Metodologia: trata-se de um estudo descritivo, do tipo relato de experiência. Results: The dynamics highlighted not only the importance of hand hygiene, but also the importance of the material resources available, the correct way to use them and the physical structure for this practice to be effective, in addition to providing the opportunity to provide signage of the areas of the hospital unit showing the step by step of hygiene, initial reason for the theme chosen for this action due to the observation of its absence at the beginning of the internship and providing pamphlets with the moments for hand hygiene. Conclusion: From this perspective, it was irrefutable that, in order to build a practice that prioritizes the constitution of the commitment of health professionals so that results are maximized for the sake of excellence in the services provided to the population, it is necessary to promote changes in attitude and work in an interdisciplinary and intersectoral way, in order to seek better results in hand hygiene.